VitroGel-loaded human MenSCs promote endometrial regeneration and fertility restoration - Wu, Meijuan; Wu, Shengnan; Tan, Shidong; Xu, Qingxin; Zhang, Donghai; Sun, Jiaxue; Yang, Haoyu; Wang, Cancan; Duan, Tao; Xu, Yao; Wei, Zhiyun (Frontiers in Bioengineering and Biotechnology, 2024)
Intrauterine adhesions (IUA), also known as Asherman's syndrome, is caused by trauma to the pregnant or non-pregnant uterus, which leads to damaged endometrial basal lining and partial or total occlusion of the uterine chambers, resulting in abnormal menstruation, infertility, or recurrent miscarriage. The essence of this syndrome is endometrial fibrosis. And there is no effective treatment for IUA to stimulate endometrial regeneration currently. Recently, menstrual blood-derived stem cells (MenSCs) have been proved to hold therapeutic promise in various diseases, such as myocardial infarction, stroke, diabetes, and liver cirrhosis. In this study, we examined the effects of MenSCs on the repair of uterine adhesions in a rat model, and more importantly, promoted such therapeutic effects via a xeno-free VitroGel MMP carrier. This combined treatment reduced the expression of inflammatory factors, increased the expression of anti-inflammatory factors, restricted the area of endometrial fibrosis, diminished uterine adhesions, and partially restored fertility, showing stronger effectiveness than each component alone and almost resembling the sham group. Our findings suggest a highly promising strategy for IUA treatment.